Strategi Pemasaran Nasi Boran Dalam Memperluas Pasar Pada Kondisi Pandemi Covid 19 (Studi Pada Penjual Nasi Boran Di Kota Lamongan) - Anak Ageng Bagas Putra Dewangga; Nurita Andriani (Management Department of Economics and Business Of Trunojoyo Madura University, 2022)
The development of the MSME sector has an important meaning in encouraging economic growth and reducing poverty in a country. One of the SMEs in Lamongan is Nasi Boran. Nasi Boran is a traditional food that has become a Micro Small Medium Enterprise (UMKM) which has become a hereditary business for the Lamongan community, especially those from Kaotan village, Sumberjo, Lamongan. The existence of the COVID-19 pandemic has an impact on the level of sales of Nasi Boran SMEs in Lamongan City which has decreased. The purpose of this study is to describe and formulate the right marketing strategy for selling Nasi Boran with a SWOT analysis approach. This study uses a purposive sampling technique by interviewing five related sources, namely the Nasi Boran seller and also one of the buyers whom the researcher happened to meet to buy boran rice as complementary data (secondary data). The results of the SWOT analysis obtained the IFAS value of 2.77 while the EFAS value of 2.16. Thus, if drawn with the SWOT Analysis Diagram, Nasi Boran UMKM is in quadrant 1 (positive, positive) where quadrant 1 is a very profitable situation. The result of choosing a competitive strategy using the SWOT Matrix is to maintain the existing market by maintaining product quality, service and also location cleanliness in order to obtain customer satisfaction. Optimizing marketing through social media to minimize the decline in purchases during the Covid 19 pandemic season.